Evolution of morphology, segmental dynamics, and conductivity in ionic liquid swollen short side chain perfluorosulfonate ionomer membranes. Issue 18 (17th June 2015) - Lin, Jun‐Hong; Colby, Ralph H.
ABSTRACT We investigate the morphology, segmental dynamics, and conductivity of 1‐ethyl‐3‐methylimidazolium trifluoromethanesulfonate (EMI‐Tf) swollen short side chain perfluorosulfonate ionomer (Aquivion) over a broad uptake range using small angle X‐ray scattering (SAXS), dielectric relaxation spectroscopy, and transient current measurement. The SAXS data indicate that the absorbed EMI‐Tf is mainly bounded in the ionic region of Aquivion. At low uptakes, EMI‐Tf acts as an effective plasticizer lowering the cluster Tg and markedly shifting the segmental relaxation to a high frequency; however, at high uptakes, the additional EMI‐Tf acts like a filler instead. A time–domain model was employed to quantify the conductivity of these membranes containing two mobile ion species, that is, cations and anions. The conductivity of both neat EMI‐Tf and EMI‐Tf swollen membranes exhibits Vogel‐Fulcher‐Tamman relation, revealing different activation parameters for ionic conduction. Furthermore, membranes containing different EMI‐Tf uptakes have similar conductivity over the reduced Tg/T axis and also follow Debye‐Stokes‐Einstein relation. Therefore, despite the abrupt change in conductivity near the critical uptake (29 wt %), both cluster Tg and segmental motion remain the key factors for the ionic conduction in these EMI‐Tf swollen membranes. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1273–1280